1999
DOI: 10.1093/genetics/151.4.1569
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Crossing Over on Mouse Synaptonemal Complexes Using Immunofluorescent Localization of MLH1 Protein

Abstract: We have used immunofluorescent localization to examine the distribution of MLH1 (MutL homolog) foci on synaptonemal complexes (SCs) from juvenile male mice. MLH1 is a mismatch repair protein necessary for meiotic recombination in mice, and MLH1 foci have been proposed to mark crossover sites. We present evidence that the number and distribution of MLH1 foci on SCs closely correspond to the number and distribution of chiasmata on diplotene-metaphase I chromosomes. MLH1 foci were typically excluded from SC in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(46 citation statements)
references
References 63 publications
4
42
0
Order By: Relevance
“…To determine whether the formation of CO was affected by HU treatment, we evaluated the number of MLH1 foci in the pachytene of mice treated with HU. In control pachytene nuclei, the average number of MLH1 foci was 22.34 per cell on autosomal SCs in agreement with the published results (Anderson et al, 1999). However, in both the high-and low-dose groups, we observed that the number decreased to 17.74 and 17.62, respectively.…”
Section: Recombination Foci In Pachytene Spermatocytes Of Mice Treated With Husupporting
confidence: 92%
See 3 more Smart Citations
“…To determine whether the formation of CO was affected by HU treatment, we evaluated the number of MLH1 foci in the pachytene of mice treated with HU. In control pachytene nuclei, the average number of MLH1 foci was 22.34 per cell on autosomal SCs in agreement with the published results (Anderson et al, 1999). However, in both the high-and low-dose groups, we observed that the number decreased to 17.74 and 17.62, respectively.…”
Section: Recombination Foci In Pachytene Spermatocytes Of Mice Treated With Husupporting
confidence: 92%
“…In this study, a common feature of recombination foci in pachytene spermatocytes of mice treated with HU was demonstrated that a large proportion of MLH1 foci located near the distal ends of SC lengths, rarely close to centromeres, suggesting this distribution of MLH1 foci relied on the SC length (Anderson et al, 1999). Moreover, the distribution of MLH1 foci in infertile men was found near the telomere and sub-telomeric regions, suggesting these regions as the hot spots for the alteration of meiotic recombination (Ferguson et al, 2009).…”
Section: Recombination Foci In Pachytene Spermatocytes Of Mice Treated With Humentioning
confidence: 56%
See 2 more Smart Citations
“…Members of a widely conserved family of RING finger proteins are also associated with ERNs and LRNs and are required for their appearance. The MutLɣ complex (Mlh1/Mlh3) is specifically associated with LRNs in many plants, fungi, and mammals, and plays an essential role in resolution of intermediates to form crossovers (Anderson et al, 1999;Rogacheva et al, 2014). C. elegans lacks a Mlh3 homolog, as do many other nematodes, and mlh-1 mutants are viable and fertile, indicating that the protein is dispensable for meiosis (Meier et al, 2018); it is not yet clear how resolvases are recruited to execute crossover resolution.…”
Section: Introductionmentioning
confidence: 99%